2023
DOI: 10.3390/ma16041370
|View full text |Cite
|
Sign up to set email alerts
|

Study on Epoxy Resin Composite Reinforced with Rice Straw Fiber

Abstract: In order to enhance the performance of the epoxy resin-prepared materials, straw fiber was used as the reinforcing base in this study. The principle of this study is to use the cellulose component exposed after the defibrillation of straw fiber can be further combined with the epoxy group. Firstly, the degree of defibrillation of straw fiber under three different pretreatment methods of acid, alkali and moist heat treatment was explored, and a control test was conducted with untreated straw fiber, which showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…Its abundance, renewability, and low cost make it an attractive candidate for sustainable material development. Furthermore, advances in chemical and mechanical processing techniques have paved the way for optimizing the compatibility between rice straw fibers and epoxy matrices, leading to improved adhesion and overall material performance [1][2][3]. Ranjan et al [2] reported the strength of rice straw fiber-reinforced epoxy biodegradable composite for the use of industrial applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its abundance, renewability, and low cost make it an attractive candidate for sustainable material development. Furthermore, advances in chemical and mechanical processing techniques have paved the way for optimizing the compatibility between rice straw fibers and epoxy matrices, leading to improved adhesion and overall material performance [1][2][3]. Ranjan et al [2] reported the strength of rice straw fiber-reinforced epoxy biodegradable composite for the use of industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, the tensile and flexural strengths of the composite decrease with increasing fiber volume fraction. Liu et al [3] claimed that the defibrillation of the straw fiber with alkali treatment was better than the acid and moisture treatment. The best performance of composites was achieved by the alkali treatment.…”
Section: Introductionmentioning
confidence: 99%